Comparison between hepatic resection and radiofrequency ablation as first‐line treatment for solitary small‐sized hepatocellular carcinoma of 3 cm or less. Issue 8 (2nd January 2013) - Imai, Kastunori; Beppu, Toru; Chikamoto, Akira; Doi, Koichi; Okabe, Hirohisa; Hayashi, Hiromitsu; Nitta, Hidetoshi; Ishiko, Takatoshi; Takamori, Hiroshi; Baba, Hideo
<x xml:space="preserve">Abstract</x> Aim It is a matter of debate whether hepatic resection (HR) or radiofrequency ablation (RFA) should be preferred for the treatment of patients with hepatocellular carcinoma (HCC). The aim of this study is to compare the long‐term outcome between HR and RFA in patients with solitary small‐sized HCC. Methods One hundred and eighty‐three patients with solitary HCC of 3 cm or less who underwent either HR (n = 101) or RFA (n = 82) as a first‐line treatment were enrolled in this study. Their cumulative disease‐free and overall survival and prognostic factors were compared. Results The disease‐free and overall survival in the HR group were significantly better than those in the RFA group for HCC of 3 cm or less; the 5‐year disease‐free and overall survival rates were 46.8% versus 23.9% and 87.5% versus 59.4% (P = 0.0008, =0.0002), respectively. In the subgroup analysis, the disease‐free and overall survival in the HR group were significantly better than those in the RFA group for HCC of more than 2 cm (P < 0.0001, <0.0001, respectively), whereas there were no significant differences between the two groups for HCC of 2 cm or less. In patients treated with RFA, a tumor size of more than 2 cm was the only independent prognostic factor for disease‐free survival (risk ratio = 1.832, P = 0.039). Conclusion HR is proposed as the first‐line treatment for patients with solitary small‐sized HCC rather than RFA, especially for those with tumors in the range 2–3 cm.